Comparative transcriptomic analysis reveals genes encoding polygalacturonase inhibitors and lectins as promising candidates conferring bruchid (Callosobruchus chinensis) resistance in moth bean (Vigna aconitifolia) - Gamage, Shyali Iroshani Rathnayaka; Takahashi, Hirokazu; Bui, Khuynh The; Nakazono, Mikio; Somta, Prakit (Agriculture and Natural Resources, 2023)
Importance of the work: Yield loss caused by the seed beetles (also known as bruchids or seed weevils) Callosobruchus chinenesis and Callosobruchus maculatus is a serious problem in several legume crops. Enhancing seed resistance to these bruchids is a major goal in legume breeding programs. Moth bean (Vigna aconitifolia) is an underutilized crop with only a few reports on genomic research. The current study used comparative RNA-seq-based transcriptomic analysis to identify candidate genes for bruchid resistance in moth bean. Objectives: To identify candidate genes for bruchid resistance in moth bean (Vigna aconitifolia), a hardy minor legume crop. Materials & Methods: The moth bean accessions TN67 (wild and resistant) and IPCMO056 (cultivated and susceptible) were grown under controlled conditions. RNA-seq-based transcriptomic analysis was performed on the immature seeds and semi-mature seeds of the two cultivars. Quantitative reverse transcription polymerase chain reaction (RT-qPCR) was used to confirm the genes with probable function for bruchid resistance that showed different expression. Results: The transcriptomic analysis showed that a gene encoding a polygalacturonate inhibitor and two genes producing lectins had differential expression. These genes were up-regulated at both the immature and semi-mature stages, albeit in each case, their expression was significantly higher in the mature stage. RT-qPCR analysis confirmed the up-regulated expression of these genes. Altogether, these results suggested that genes encoding a polygalacturonase inhibitor and lectins could be candidate genes for bruchid resistance in moth bean. Main finding: Genes relating to plant defense in the seeds of moth bean were identified. Genes encoding a polygalacturonase inhibitor and lectins were identified as candidate genes conferring bruchid resistance in the moth bean accession TN67.